Bidding strategies for virtual power plants in the Iberian electricity market - Gough, Matthew (2021)
In recent years, the energy sector has undergone major changes, particularly in Portugal, where there is complete liberalization of the electricity sector. Like in other European countries, a market agent has been created to facilitate trading relations between producer and trader. The Virtual Power Plant (VPP) agent aims to minimize the costs to the trader and maximizes the profits of producers. In this work, five renewable power plants, which are contractually linked with a VPP, are analyzed to verify the profitability of these contracts for both parties. Using this framework, an analysis is carried out examining the differences between actual renewable production and the planned (forecasted) production. In some instances, there are significant deviations between actual and forecast production and this results in higher costs. Consequently, the greater the deviations, the greater the expenses and, therefore, the lower the profit of each party. Thus, new bidding strategies that result in the reduction of these differences are sought. The bidding strategies proposed in this paper involve markets and various types of contracts to deliver the optimal solution that results in higher profits for both parties. The results show an increase in VPP profit on average of 32%